Postmastectomy radiotherapy in pN1 breast cancer: Survival outcomes and prognostic factors from a single-institution cohort - Raksha M. Narasimhan; Aren Singh Saini; Kayla Samimi; Ifeanyichukwu Ogobuiro; Xuesen Zhao; Sunwoo Han; Cristiane Takita; Crystal S. Taswell (PLoS ONE, 2026)
Purpose/Objectives The role of postmastectomy radiotherapy (PMRT) in patients with pathologic N1 (pN1) breast cancer, including triple-negative breast cancer (TNBC), remains controversial in the era of modern systemic therapy. We evaluated the association between PMRT and recurrence-free survival (RFS) and overall survival (OS) and identified prognostic factors in a contemporary single-institution pN1 cohort. Materials/Methods We retrospectively reviewed female patients with pT1-2N1M0 breast cancer treated with mastectomy between 1999 and 2023. RFS and OS were estimated using Kaplan-Meier methods and compared by PMRT status with log-rank testing. Univariable Cox proportional hazards models assessed associations between clinical factors—including tumor laterality, receptor subtype (TNBC vs non-TNBC), nodal burden, and adjuvant therapies—and survival outcomes, with subgroup analyses by PMRT status and receptor subtype. Results Fifty-seven patients were included; 22 (38.6%) received PMRT. With a median follow-up of 85 months, PMRT was not associated with improved RFS (median 133 vs 120 months; p = 0.256) or OS (not reached vs 195 months; p = 0.154). Hormone therapy was significantly associated with improved RFS (HR 0.43; p = 0.026) and OS (HR 0.13; p = 0.003), while having 2–3 positive lymph nodes predicted worse RFS (HR 2.86; p = 0.007). No significant differential benefit from PMRT was observed in patients with TNBC or non-TNBC disease. Conclusions PMRT was not associated with a survival benefit in this pN1 cohort, including patients with TNBC. Interpretation is limited by modest sample size and statistical power. Outcomes appeared driven by tumor biology, nodal burden, and systemic therapy, supporting individualized PMRT decision-making.